(untitled) (Metallurgy and Foundry Engineering, 2009)
This paper describes FEM simulations and experiments of the hydroforming process, which were carried out using test stand and ABAQUS/CAE software. The application of simulation methods to the development of the hydroformed parts was illustrated. The influence of the forming conditions, such as the loading path of the hydraulic pressure and the axial feeding, on the hydroforming of Y-shapes was investigated. These estimated conditions were improved in FEM simulations and then verified with hydroforming experiment. A tube made of stainless and unalloyed steels were taken into consideration both in a numerical and experimental study. The experimental investigation shows considerable influence of the mechanical properties of the examined steel grades on the metal flow and final shape, especially the thickness distributions and the branch height. The results from the experiment and FEM simulation, e.g. loading path, thickness distributions or branch height were in good agreement. This means that numerical simulation is a good way to evaluate the part formability.